PERCEPTION OF NEIGHBORHOOD AROUND THE REAL ESTATE PHYSICAL BOUNDARY - Tin Budi Utami (SINERGI, 2019)
The presence of real estate in South Tangerang cannot be separated from a surrounding settlement or new settlements that grew later. Regulation and design are more set-in real estate planning so that real estate tends to form an enclave for security and social image. Forming some type of physical boundary with surrounding residential of real estate perceived vary both by residents and outside the real estate. This study aims to map out how the perception of the surrounding community to the physical boundaries of real estate on a cluster pattern made by the developer, with research sites in Bintaro Jaya, South Tangerang. The method used observation and structured interviews with communities. The surrounding community has very positively responded to the presence of real estate, but the relationship with the institution is perceived as not useful because of the boundary design is more detrimental for them. Their participation in the plan has not been well accommodated so that access is closed unilaterally by the developer.The presence of real estate in South Tangerang cannot be separate from a surrounding settlement or new settlements that grew later. Regulation and design are more set-in real estate planning so that real estate tends to form an enclave for security and social image. Forming some physical boundary with surrounding residential of real estate perceived vary both by residents and outside the real estate. This study aims to map out how the perception of the surrounding community to the physical boundaries of real estate on a cluster pattern made by the developer, with research sites in Bintaro Jaya, South Tangerang. The method used observation and structured interviews with communities.The surrounding community has very positively responded to the presence of real estate, but the relationship with the institution is perceived as not useful because the boundary design is more detrimental for them. Their participation in the plan has not been well accommodated so that access is closed unilaterally by the developer.